Egg masses and development of Falsilunatia eltanini (Mollusca: Gastropoda): a deep-sea naticid from a Southwestern Atlantic Canyon - Averbuj, Andres (2018)
A series of cruises to the Mar del Plata Submarine Canyon (38°S/54°W) off Argentina in 2012–2013 have provided biological material that enables insights into the various modes of development of deep-sea invertebrates at depths up to 3500 m. This study describes the unusually large encapsulated embryos of the globose moon snail, Falsilunatia eltanini Dell, 1990 (Naticidae), and compares them with another direct-developing naticid from the same collections, Bulbus carcellesi. Embryos of F. eltanini develop in sand ribbon egg masses that contain up to 6 conspicuous egg capsules, 5.0–8.5 mm diameter. Each F. eltanini egg capsule contains a single, ~ 170-µm diameter egg and abundant, white, supplementary food. This allows the crawling pre-hatching juveniles to grow to 4.7 mm shell diameter. Different stages of development were found among multiple egg collars collected on the same date, which suggests a long reproductive season that could be continuous or periodic (lasting more than a year). The number of whorls in the hatchling juvenile shells and the significant size they attain confirm the occurrence of a long period of embryonic development. This reproductive strategy requires a large maternal investment in the very large egg capsules and abundant supplementary food. Within Naticidae, this extraordinary modality is only observed in several species inhabiting deep-sea and boreal cold waters.